Improvement of an assembly process front seat to cars using system dynamics simulation - Pérez Rave, Jorge; Parra Mesa, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper, a methodology to improve the assembly process front seat to cars is present. To improve this process the system dynamics simulation was used. The result of the assembly process in various experimental conditions was analyzed. Changes in workforceÂ´s quantity and distribution and in jobs integration were simulated. As results of this study, a simulation model that reasonably represents the dynamic behaviour of the process and two improvement strategies were obtained. The strategy first with an investment few was implemented. As result of this, the process’s productivity in 12% was incremented and the personnel’s idle time in 44% was reduced. The strategy second ";Integration of workplaces” was denominate and bests results to can obtains.